Literature reviews of stroke with hypereosinophilic syndrome - Ryohei Ono (Elsevier, 2021)
Hypereosinophilic syndrome (HES) is defined by persistently elevated blood eosinophil levels and is associated with evidence of organ damage. Cardiovascular involvement in HES is most commonly associated with Loffler endocarditis (cardiac HES). Cardiac HES is typically characterized by progressive subendocardial fibrosis with overlying mural thrombus formation, leading to restrictive dysfunction of the left ventricle. The thrombus from cardiac HES could result in cardiogenic stroke; however, most of the stroke cases with HES were not associated with huge thromboembolism rather multiple infarcts in the watershed area. The major clinical features of 97 previously reported cases of stroke with HES are as follows: the median age was 52 years, of which 61 (63%) were men; the initial presenting symptoms were neurological (73%), followed by headache (16%), respiratory symptoms (9%), and visual symptoms (9%). Almost half of the cases were diagnosed with cardiac HES. The characteristics of cardiac findings were mural thrombi, endomyocardial fibrosis, and a restrictive pattern of heart failure. Cerebral findings revealed 78 cases (80%) were described as multiple infarctions and 55 cases (57 %) were involved with watershed areas, whereas 11 cases (11％) were described as embolic stroke for one proximal large-vessel occlusion. Regarding treatment, 71 (73%), 28 (29%), and 16 (16%) patients were treated with steroids, anticoagulants, and antiplatelets, respectively. The overall mortality and recovery rates were 11% and 89%, respectively. Physicians should know most cases of stroke with HES are characterized by multiple infarctions in the watershed area, and cardiac HES is not always associated with stroke.